Will Nigella sativa oil protect parotid glands of rats against cranium gamma irradiation? Histological and immunohistochemical evaluation - Salwa Farid Ahmed; Mostafa A. Bakr (BMC, 2024)
Abstract Background Radiation plays an essential role in treating malignancies. Radiation exposure of salivary glands often results in permanent loss of their functions; therefore, their protection against radiation is crucial. Nigella sativa oil (NSO) is a useful antioxidant against free radicals. The purpose of this study was to investigate the radio-protective effect of NSO on oxidative injury of parotid glands of gamma-irradiated rats. Methods: Twenty-eight male albino rats were divided into four groups (n = 7): Group 1: Neither NSO nor radiation, Group 2: Rats received NSO 400 mg/kg, Group 3: Rats received 15 Gy cranium gamma irradiation & Group 4: Rats received gamma irradiation and NSO. Rats were sacrificed two weeks after the last NSO dose. Histological sections of parotid glands were stained with H&E, Masson's trichrome and anti-TGF-β antibodies. Area percentage of Masson's trichrome and TGF-β expression was morphometrically examined. Results: Parotid glands of control and NSO groups revealed normal morphology. Gamma-irradiated glands showed loss of normal acinar architecture and slight acinar shrinkage. NSO treatment of gamma-irradiated glands preserved acinar outline and architecture. Masson's trichrome stained samples revealed trace amounts of collagen fibers in control and NSO groups, and excessive amounts of collagen fibers in gamma-irradiated group, in addition to few collagen fibers for gamma-irradiated glands treated with NSO. Additionally, control and NSO groups showed negative TGF-β expression. Gamma-irradiated group showed high TGF-β expression, while NSO treated gamma-irradiated group showed moderate TGF-β expression. Conclusions: Gamma-irradiation adversely affected parotid glands, and in contrast, NSO seemed to positively counteract this adverse effect.